(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Learning a foreign language opens doors to new cultures, opportunities, and personal growth. However, achieving proficiency in a foreign language requires a well-structured approach, combining dedication, effective strategies, and consistent practice. This article outlines the essential guidelines for proficient foreign language learning, focusing on evidence-based methods such as immersion, spaced repetition, active communication, and the use of modern technology. Additionally, it addresses the importance of setting realistic goals, managing motivation, and incorporating cultural understanding in the language-learning process.